A Suggested Integrated Framework to Foundation: the Libyan Institute of Internal Auditors: "A Pilot Study" - Moutaz Abdelhamied Ali Kablan (Scientific Journal of University of Benghazi, 2018)
The aim of this study is to state a suggested integrated framework to the foundation the Libyan Institute of internal auditors. The absence of a professional existence to care about the internal auditors performance in Libya has stimulated this study to achieve the previous goal. Memorable, the study was parted to three sections, the first one about the methodology of this study, the second section has illustrated the pioneer experiences of the western and Arabian countries about foundation of their institutes of internal auditors alike, to reason a suggested integrated framework to the foundation of the Libyan Institute of internal auditors, while the third one has presented the pilot aspect, which demonstrated the approval of the academics, the chairmen of multi companies, the external auditors, the internal auditors and others about the importance of the foundation of the Libyan Institute of internal auditors in the Libyan business environment in general.